UJI ANTIINFLAMASI EKSTRAK METANOL DAUN SIRIH MERAH (Piper crocatum Ruiz & Pav ) PADA TIKUS PUTIH - Atik Fitriyani; Lina Winarti; Siti Muslichah; Nuri Nuri (Majalah Obat Tradisional, 2011)
Inflammation is a natural respon for tissue damage. To reduce inflammation, people used a NSAID (Non Steroid Antiinflammatory Drugs). This agent caused many side effects. One of medicinal plant empirically used for traditional medicine is Piper Crocatum Ruiz & Pav. This plant is potential to be developed as medicine for anti-inflammatory because its contains flavonoid, saponin, tannin, and alkaloid. The aim of this study was to investigate the anti-inflammatory effect of the P.Crocatum extract  using carrageenan-induced rat oedema test. For the anti-inflammatory activity measurement, five different groups were established and piper extract was administered  in three different doses : 25, 50 and 100 mg/kgBW. Acetosal was used as a reference agent. It was found that reduction in the flammation was 77.58% for acetosal,  72.37% for 25 mg/kg extract, 85.60% for 50mg/kg, and 81.02% mg/kg for 100mg/kg extract. Extract of P. Crocatum at 50 mg/kg showed the strongest anti-inflammatory activity among the doses used. The results showed that P. Crocatum extract posseses promising anti-inflammatory effect.